Pediatric Gastrointestinal Interventions - Chennapragada, S. Murthy (Digestive Disease Interventions, 2024)
Image-guided interventions are increasingly being used in the management of many pediatric disease processes since they provide safe and effective minimally invasive treatment options. This review article attempts to provide an overview of the commonly performed interventions in the gastrointestinal tract in children. These include esophageal balloon dilatation, establishment and maintenance of gastroenteral access, and hepatobiliary interventions (liver biopsy, percutaneous cholangiogram, and biliary drainage).
Keywords: pediatric interventional radiology; gastrointestinal; esophageal dilatation; gastrostomy; percutaneous cholangiogram